(untitled) (Research, Society and Development, 2022)
The article seeks to study the property and cultural landscape through a case study of the Manzo Nigunzo Kaiango Quilombola Community, from district Santa Efigênia, in the city of Belo Horizonte,in the State of Minas Gerais, Brazil. Based on the history of recognition of property and recognition of the community’s intangible heritage by the municipality, there is a reflection on which elements of the urban quilombola landscape would serve as objective requirements for recognition and seal of the quilombola cultural landscape. The dialectical method will be used, with use and criticism ofOrdinance IPHAN No. 127 of April 30, 2009, with a case study.